Identifying the characteristics of top-level male volleyball players' jump performance by examining their stretch-shortening cycle exercise - Okano, K.; Yamanaka, H.; Kuki, S.; Tanigawa, S. (Japan Journal of Physical Education, Health and Sport Sciences, 2017)
This study examined for the first time the correlation between the spike jump (SPJ), an action specific to volleyball, and other jumps among 202 top-level male volleyball players from domestic leagues (84 from the V. League and 118 from the first division of the Kanto University Volleyball Association). We then categorized the ability of the players during stretch-shortening cycle exercise (SSC) to examine the characteristics of SPJ performance and other positions. The results indicated that, on the one hand, ability in both the counter movement jump (CMJ) and rebound jump (RJ) is required for the SPJ, RJ showing more prominence among elite players. On the other hand, for SSC ability, exercise requiring a longer duration, such as the CMJ, was found to be more critical for the SPJ with a one-step run-up. In terms of different player positions, the results suggested that a middle blocker (MB) with a shorter run-up required a jump that exerts force through longer-duration SSC exercise, whereas a wing spiker (WS) with a full run-up demonstrated more ballistic SSC exercise in his jump. On the basis of these findings, this study has shown the importance of evaluating the characteristics of jump performance according to each player position when designing or choosing the most appropriate physical training exercises for volleyball players.